1992
DOI: 10.2105/ajph.82.2.243
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of Medicare's hospital claims data: progress has been made, but problems remain.

Abstract: BACKGROUND. Health care databases provide a widely used source of data for health care research, but their accuracy remains uncertain. We analyzed data from the 1985 National DRG Validation Study, which carefully reabstracted and reassigned ICD-9-CM diagnosis and procedure codes from a national sample of 7050 medical records, to determine whether coding accuracy had improved since the Institute of Medicine studies of the 1970s and to assess the current coding accuracy of specific diagnoses and procedures. METH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
335
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 654 publications
(350 citation statements)
references
References 31 publications
(4 reference statements)
12
335
0
1
Order By: Relevance
“…By using an administrative database, we find inherent and well known shortcomings [10,11]. The main shortcomings are related to the little and not very specific clinic information contained, especially as regards to the treatments given to the patient, patient´s precedents and risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…By using an administrative database, we find inherent and well known shortcomings [10,11]. The main shortcomings are related to the little and not very specific clinic information contained, especially as regards to the treatments given to the patient, patient´s precedents and risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Disease surveillance and quality‐of‐care studies frequently use information from administrative claims databases, such as Medicare, by identifying patients with specific conditions based on International Classification of Diseases, Ninth Revision, Clinical Modification (ICD‐9‐CM) codes. Studies comparing the accuracy of ICD‐9‐CM codes with medical record review find variations in agreement depending on code selection,2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18 as well as patient characteristics, such as age, race/ethnicity,10, 11 sex,11 and length of hospitalization 3. Aside from teaching hospital status10 and hospital departments,16 potential variations in accuracy based on other hospital characteristics are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In a landmark coding validation study, Fisher, et al, (1992) reabstracted and reassigned ICD-9-CM diagnosis and procedure codes from a national cross-section 6 of medical records. They sought to provide an assessment of coding accuracy of specific diagnoses and procedures.…”
Section: Related Studiesmentioning
confidence: 99%
“…They determined that the percentage of agreement between the principal diagnosis on the re-abstracted record and the original hospital record, when analyzed at sublevels of classification, improved slightly, but the accuracy of diagnosis and procedure coding varied substantially across conditions. They concluded that variability in the accuracy of diagnosis coding continued to pose a problem that must be overcome if classification research is to achieve its full potential (Fisher, et al, 1992).…”
Section: Related Studiesmentioning
confidence: 99%